2005
DOI: 10.1002/jso.20329
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-lymphocyte ratio as a prognostic factor in colorectal cancer

Abstract: Pre-operative NLR may represent a simple method of identifying colorectal cancer patients with a poor prognosis pre-operatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
845
6
13

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,002 publications
(929 citation statements)
references
References 21 publications
26
845
6
13
Order By: Relevance
“…Several studies suggested that the neutrophilto-lymphocyte ratio was a prognostic factor for colorectal and non-small cell cancer. Other studies revealed that the neutrophil-to-lymphocyte ratio was related to poor prognosis (Walsh et al, 2005;). The results of the current study suggest that the presence of a systemic inflammatory reaction at diagnosis was an independent predictor of poor long-term cancer outcomes in patients with localized prostate cancer (McArdle et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Several studies suggested that the neutrophilto-lymphocyte ratio was a prognostic factor for colorectal and non-small cell cancer. Other studies revealed that the neutrophil-to-lymphocyte ratio was related to poor prognosis (Walsh et al, 2005;). The results of the current study suggest that the presence of a systemic inflammatory reaction at diagnosis was an independent predictor of poor long-term cancer outcomes in patients with localized prostate cancer (McArdle et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Pre-treatment elevated NLR was first described by Walsh et al (2005) as a useful prognostic indicator in CRC. After that, emerging evidences from several studies have pointed out that NLR has a prognostic value in patients with pancreatic (Aliustaoglu et al, 2010), breast (Azab et al, 2012), lung (Kaya et al, 2013;Unal et al, 2013) and gastric (Jung et al, 2011) cancers.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand some reports have studied different stages like we did, while others analyzed specific stage of patients in terms of survival analysis. Ding et al (2010) studied only stage IIA patient; on the contrary Walsh et al (2005) studied all Dukes stages patients. Additionally, Halazun et al (2008) found that elevated NLR increases both risk of death and the risk of recurrence in patients who undergo surgery for CRC liver metastases.…”
Section: Discussionmentioning
confidence: 99%
“…[158] Colorectal cancer The NLR was higher in advanced stages of cancer. The ability to produce ROS at the terminal stage was 33 % lower than in the control group.…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 99%